2020
DOI: 10.1073/pnas.2015292118
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Purkinje cells can differentially modulate coherence between sensory and motor cortex depending on region and behavior

Abstract: Activity of sensory and motor cortices is essential for sensorimotor integration. In particular, coherence between these areas may indicate binding of critical functions like perception, motor planning, action, or sleep. Evidence is accumulating that cerebellar output modulates cortical activity and coherence, but how, when, and where it does so is unclear. We studied activity in and coherence between S1 and M1 cortices during whisker stimulation in the absence and presence of optogenetic Purkinje cell stimula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 91 publications
4
37
0
Order By: Relevance
“…Changing SS firing during the no-lick period affects choice performance and licking Given that SS firing during the no-lick period was associated with choice, and as SS firing in crus 1 and 2 is related to licking (Bryant et al, 2010), we addressed whether a change in SS firing could affect lick timing as well as choice performance. Pcp2-ChR2 mice have PC-specific expression Channelrhodopsin, allowing optogenetic SS stimulation and creating transient disruption of cerebellar nucleus neuron firing (Figures S6A and S6E) (Romano et al, 2018;Witter et al, 2013;Lindeman et al, 2021).…”
Section: Pcs Also Encode Lickingmentioning
confidence: 99%
“…Changing SS firing during the no-lick period affects choice performance and licking Given that SS firing during the no-lick period was associated with choice, and as SS firing in crus 1 and 2 is related to licking (Bryant et al, 2010), we addressed whether a change in SS firing could affect lick timing as well as choice performance. Pcp2-ChR2 mice have PC-specific expression Channelrhodopsin, allowing optogenetic SS stimulation and creating transient disruption of cerebellar nucleus neuron firing (Figures S6A and S6E) (Romano et al, 2018;Witter et al, 2013;Lindeman et al, 2021).…”
Section: Pcs Also Encode Lickingmentioning
confidence: 99%
“…We propose that the cerebellum contributes to the cognitive process of SWM decision-making by optimizing the task-related modulation of mPFC-dCA1 gamma coherence. A proposed role of the cerebellum in optimizing task related coherence between frontal cortical areas and hence optimizing neuronal communication in a task related manner is also supported by experimental evidence in the sensorimotor domain (Lindeman et al, 2021;Popa et al, 2013). Popa et al showed that inhibiting cerebellar output from the interposed nuclei in awake, head fixed mice reduced gamma coherence between sensory and motor cortical areas (Popa et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Popa et al showed that inhibiting cerebellar output from the interposed nuclei in awake, head fixed mice reduced gamma coherence between sensory and motor cortical areas (Popa et al, 2013). Lindeman and colleagues demonstrated cerebellar involvement in a task related modulation of theta and gamma coherence between sensory and motor areas involved in active whisker movements (Lindeman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebello-hippocampal connections have been found via the ventrolateral and laterodorsal thalamus in mice (Bohne et al, 2019) that needs further investigation in humans. However, for our computational simulation based on a published model (Yousif et al, 2020), we postulated an effect of cerebellar tES on substance-seeking triggered by substance-associated cues since interactions between sensory and motor cortices can be modulated by the cerebellum (Lindeman et al, 2021). While ctDCS of the DCN induced gamma oscillations (top panel of Figure 9), bottom panel of the Figure 9 shows that tTIS of the DCN at 63Hz amplitude modulation could lead to gamma-to-beta frequency shift.…”
Section: Computational Modelling Of Ctdcs Of Inferior Frontal Gyrus and Ttis Of Dcnmentioning
confidence: 99%